Towards a taxonomy of Pleuromyces (Agaricomycetes): a new species of P. fauriei from Russia described and the status of the genus within the Agaricales reconsidered - Malysheva, Ekaterina F.; Svetasheva, Tatiana Yu.; Bondarchuk, Svetlana N. (Phytotaxa, 2025)
One new species, Pleuromyces fauriei, is described and illustrated here based on collections from the Russian Far East. The new data contribute to the taxonomy of the genus Pleuromyces, which until now was considered monotypic, with a single species, P. hungaricus, originally described from Hungary. The species delimitation was supported morphologically and molecularly, and the main distinguishing characteristics were discussed. Based on the study of the newly described species, the morphological criteria of the genus as a whole were also corrected and clarified. The taxonomic position of the genus Pleuromyces was revised on the basis of an extended phylogenetic analysis of two DNA regions: the large subunit of nuclear ribosomal RNA gene (nrLSU) and the internal transcribed spacer regions (nrITS), involving representatives of several families of Agaricales. The data obtained do not confirm the placement of the genus in the family Tubariaceae. At this stage of knowledge, it is proposed to consider the genus as a taxon with the incertae sedis status.